Strategi Self-Regulated Learning Untuk Menurunkan Tingkat Prokrastinasi Akademik Siswa Pada Tugas Program Linier - Asfira Zakiatun Nisa'; Marhayati, Marhayati; Masamah, Ulfa (Pusat Studi Pengembangan Pembelajaran Matematika, 2022)
This study aimed to reduce the level of students' academic procrastination on mathematical tasks in linear programming materials through the Self-Regulated Learning strategy. The type of research used is Classroom Action Research (CAR) which consists of two cycles. One cycle consists of four stages, namely planning, implementation, observation, and reflection. The study was conducted on students of class XI IPA 4 MAN 1 Blitar. Data collection techniques using questionnaires. Data analysis used descriptive analysis. The results of the analysis showed that the average level of academic procrastination of students at the pre-cycle stage was 80.896%, the average level of student academic procrastination at the stage of the first cycle was 75.66%, and the average level of student academic procrastination at the stage of the second cycle was 62.23%. The three data indicate a decrease in students' academic procrastination on mathematics assignments on linear programming material from pre-cycle to cycle I by 5.236% and from cycle I to cycle II by 13.43%. Thus, using the Self-Regulated Learning strategy in learning impacts the academic procrastination of class XI IPA 4 MAN 1 Blitar students. The positive effects of implementing Self-Regulated Learning in the classroom are shown by students being more active in doing math tasks, thereby reducing academic procrastination, especially in linear programming.